Monitoring the glycosylation of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionate‐type glutamate receptors using specific antibodies reveals a novel regulatory mechanism of N‐glycosylation occupancy by molecular chaperones in mice. Issue 5 (6th February 2020) - Midorikawa, Ryosuke; Takakura, Daisuke; Morise, Jyoji; Wakazono, Yoshihiko; Kawasaki, Nana; Oka, Shogo; Takamiya, Kogo
Abstract: In the mammalian nervous system, protein N‐glycosylation plays an important role in neuronal physiology. In this study, we performed a comprehensive N‐glycosylation analysis of mouse GluA1, one of the major subunits of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionate type glutamate receptor, which possesses six potential N‐glycosylation sites in the N‐terminal domain. By mass spectrometry‐based analysis, we identified the N‐glycoforms and semiquantitatively determined the site‐specific N‐glycosylation occupancy of GluA1. In addition, only the N401‐glycosylation site demonstrated incomplete N‐glycosylation occupancy. Therefore, we generated a peptide antibody that specifically detects the N401‐glycan‐free form to precisely quantify N401‐glycosylation occupancy. Using this antibody, we clarified that N401 occupancy varies between cell types and increases in an age‐dependent manner in mouse forebrains. To address the regulatory mechanism of N401‐glycosylation, binding proteins of GluA1 around the N401 site were screened. HSP70 family proteins, including Bip, were identified as candidates. Bip has been known as a molecular chaperone that plays a key role in protein folding in the ER (endoplasmic reticulum). To examine the involvement of Bip in N401‐glycosylation, the effect of Bip over‐expression on N401 occupancy was evaluated in HEK293T cells, and the results demonstrated Bip increases the N401 glycan‐free form by mediating selective prolongation of its protein half‐life. Taken together, we propose that the N401‐glycosite of GluA1 receives a unique control of modification, and we also propose a novel N‐glycosylation occupancy regulatory mechanism by Bip that might be associated with α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionate receptors function in the brain. Abstract : Left: 401N‐glycosylated GluA1, which would be properly folded without Bip binding in ER lumen, are dominantly transported to PM after de novo synthesis. Right: compared to 401N‐glycosylated GluA1, de novo synthesized 401N‐glycan‐free GluA1 are relatively unstable, resulting in rapid degradation. Bip selectively binds to the 401N‐glycan‐free GluA1 and assists proper folding. This extends the protein half‐life of 401N‐glycan‐free GluA1 and could increase its expression level at PM. The thin and thick arrows indicate inactive and active pathways under the greater Bip expression, respectively. PM, plasma membrane; ER‐M, ER membrane.